The Impact of Value Added Intellectual Coefficient Components on Financial Health - Faris Nasif AL-SHUBIRI (Revista de Management Comparat International)
The success of any sector in the financial market depends on how administrators can manage their companies? And this case reflected on the success in the market, which is characterized by intense competition and this also depends on the creativity and the technology used, which includes knowledge, experience and skills. This study therefore tries to investigate the impact of value added intellectual coefficient components on financial health in Jordanian industrial sector listed in Amman Stock Exchange. The results were based on the data taken from 11 industrial sectors from 2005- 2011. The results indicates a statistically significant impact of human, employed element and intellectual capital as whole and financial health as productivity and profitability dependent variables at a strong level 1% but statistically significant structural capital with the dependent variable is liquidity at a strong level 1%. The researcher recommends attention to the assets of knowledge and encourages the efforts of human development, training and motivating them while giving flexibility to employees for the purposes of creativity and innovation.